A Comparison of Chinese and Colombian University EFL Students Regarding Learner Autonomy - Ximena Paola Buendía Arias (Universidad Nacional de Colombia, 2015)
This research seeks to gain deeper understanding of learner autonomy in English as a Foreign Language students from different cultures through the identification and analysis of similarities and differences between Chinese and Colombian students from two public universities: Tianjin Foreign Studies University in China and Universidad Surcolombiana in Colombia. Data were gathered using questionnaires and interviews for comparative research. The participants' responses were analyzed using quantitative methods such as independent samples t-test and qualitative methods such as data codification and triangulation were also used. The results indicate a significant difference between the two groups of learners regarding their autonomy. Complementarily, their autonomy-enhancement difficulties were diagnosed.